2013
DOI: 10.2340/16501977-1131
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the feasibility of Goal Attainment Scaling as a rehabilitation outcome measure for veterans

Abstract: The goal attainment scaling approach was seen to support a client-focussed approach to rehabilitation. Data obtained through the use of goal attainment scaling can be summarised at different levels to be useful for clients, providers, rehabilitation coordinators, and senior executives to monitor and report on the overall success of the different types of rehabilitation provided to veteran clients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Six of the identified tools were described and studied in five or more articles. These included Goal Attainment Scaling including Goal Attainment Scaling for Major Depressive Disorder and Goal Attainment Scaling for Upper Limb Spasticity 2857,113,114,118143,150,172,181 ( n = 61), Canadian Occupational Performance Measure 6,2527,101,103…”
Section: Resultsmentioning
confidence: 99%
“…Six of the identified tools were described and studied in five or more articles. These included Goal Attainment Scaling including Goal Attainment Scaling for Major Depressive Disorder and Goal Attainment Scaling for Upper Limb Spasticity 2857,113,114,118143,150,172,181 ( n = 61), Canadian Occupational Performance Measure 6,2527,101,103…”
Section: Resultsmentioning
confidence: 99%
“…Besides complementing standard outcome measures to more effectively measure change, the large effect size observed suggests that GAS‐Hēm may be considered a co‐intervention. Other studies incorporating GAS have indicated that its use may have motivated some to address their challenges with greater effort and persistence . Additionally, although no intervention was required, in some cases interventions (eg education, training and change in care plan) were implemented and may account for some of the observed changes.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies incorporating GAS have indicated that its use may have motivated some to address their challenges with greater effort and persistence. 9,18,22 Additionally, although no intervention was required, in some cases interventions (eg education, training and change in care plan) were implemented and may account for some of the observed changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To consider the implementation of GAS in routine clinical practice, it must be administered in a timely (<15 minutes average examination time) and consistent (checklist adherence >80%) manner. The GAS process, feasibility, and fidelity will be evaluated by measuring the time (in minutes) to perform the GAS process, checklist adherence (as a percentage), and the nature of the goals identified (using the ICF domains) [ 45 , 46 ]. Interrater reliability of GAS scores will be assessed by examining the association between 2 independent physical therapist examiners using the Spearman rank correlation [ 33 ].…”
Section: Methodsmentioning
confidence: 99%